2011
DOI: 10.1136/jclinpath-2011-200064
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic molecular markers in women aged 35 years or younger with breast cancer: is there a difference from the older patients?

Abstract: For women ≤ 35 years, TP53 mutations, Ki67 and HER2 expressions are strong prognostic factors. The limited prognostic value of hormone receptors suggests that the prognostic markers used in age-unspecified breast cancer may not be completely fit for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…After screenings, 68 articles were chosen for further full-text review. Ultimately, 32 eligible studies were included in our meta-analysis59101112131415161718192021222324252627282930313233343536373839 (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…After screenings, 68 articles were chosen for further full-text review. Ultimately, 32 eligible studies were included in our meta-analysis59101112131415161718192021222324252627282930313233343536373839 (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…These results could partly be explained by the fact that young women are diagnosed more often at advanced stages, present unfavorable tumour characteristics or have a family history of breast cancer [6][7][8][9]. In a very recent study of Lin et al it is suggested that these cancers occurring at a very young age may be considered as a distinct disease entity [10]. Due to the relatively low frequency of breast carcinomas in women aged ≤35 years there are few data on how risk factors predict breast cancer in younger women and the prognostic factors in this group have yet to be established.…”
Section: Introductionmentioning
confidence: 89%
“…In the study of Lin et al it is presented that for women ≤35 years high Ki67 expression, TP53 mutations, ER negative status and HER2 overexpression were associated with shorter overall survival, and TP53 mutations, Ki67, HER2 overexpression are strong prognostic factors for these women [10].…”
Section: Introductionmentioning
confidence: 99%